Reticence and willingness to communicate (WTC) of East Asian language learners. (December 2016) - Shao, Qing; Gao, Xuesong (Andy)
Abstract: In this virtual special issue editorial, we examine the claims put forward by studies concerning East Asian language learners' reticence and willingness to communicate ('WTC') published in System between 2000 and 2015. The selected articles have explored why and how language learners are willing to participate or choose to be reticent in classroom activities in a variety of contexts including Japan, Korea, Mainland China, Hong Kong, Macau, New Zealand, and Taiwan. The findings encourage language teachers to involve East Asian language learners in pedagogical activities as these learners are not culturally conditioned to be silent and passive. The selected articles also remind language teachers of the importance of managing various individual and contextual factors underlying these learners' willingness to communicate in classes. With this editorial, we invite our readers to react to the selected articles and help us deepen engagement with these issues so that we can promote language learners' classroom participation.